The Impact of Capital Structure, Firm Size, Growth, And Profitability on Firm Value - Irsad, Moch; Sudarsi, Sri; Kartika, Andi (EconBank: Journal of Economics and Banking, 2023)
The study aims to be carried to ascertain the effect of capital structure, firm's size, growth, and profitability upon firm value. Previous research on corporate value produced inconsistent results, indicating that more research is required to assess firm worth. In the 2019-2021 period, Third-party information in the structure of annual reports on transportation sector firms collected from the IDX site is applied by researchers. Purposive sampling was utilized in this study. Data analysis approaches such as descriptive statistical analysis and multiple linear regression analysis were used in this study. First, descriptive statistics, classical hypothesis testing, multiple linear regression analysis, and hypothesis testing are accomplished. According to the results of this study, firm size and profitability have an impact on firm value, however capital structure and growth have no impact on firm value.